Strengthening The Quality of Madrasah Services through Human Resource Management - Dakir, Dakir (JURNAL AL-TANZIM, 2022)
This study aims to analyze human resource management in improving the quality of madrasa services at MTs Negeri Model Palangkaraya. This research uses a qualitative case study approach, where the researcher uses interviews, observations, and documentation in collecting data. The data analysis was carried out by referring to the Miles and Huberman concept: data collection, data reduction, data presentation, and conclusion. The results of the study indicate that human resource management in improving the quality of madrasa services is carried out through; the determination of service quality targets, analysis of human resource needs, fulfillment of human resource needs, and evaluation of human resource performance. This study has implications for the importance of madrasah in preparing the quality of the human resources in them to provide excellent service to the community and meet expectations.